PERANCANGAN MODEL-VIEW-CONTROLLER PADA APLIKASI PERPUSTAKAAN SEKOLAH - Jhon Very (STIKOM CKI, 2017)
Information system for library can enhance its services such as process of borrowing and returning collection quickly and accurately. In this article, we present a system which is developed by implementation of Model-View-Control architecture in order to make components within the system more independent to each other. The system was developed for the existing process business in the library of Al-Azhar 1 Junior High School. The existing system is so rigid that further development for additional features is almost impossible. The currently developed system by adopting MVC design pattern provides better reusability in object-oriented programming paradigm hence adding a new feature is much more feasible.Keywords: Model-View-Controller (MVC), Sistem Perpustakaan